Cytokine Gene Expression Profiles during HIV and Helminth Coinfection in Underprivileged Peri-Urban South African Adults - Miranda N. Mpaka-Mbatha; Pragalathan Naidoo; Khethiwe N. Bhengu; Md. Mazharul Islam; Ravesh Singh; Nomzamo Nembe-Mafa; Zilungile L. Mkhize-Kwitshana (Diagnostics, 2023)
Background: Intestinal helminth parasites are potent stimulators of T helper type 2 (Th2) and regulatory Th3 anti-inflammatory immune responses, while human immunodeficiency virus (HIV) infections are activators of predominantly T helper type 1(Th1) pro-inflammatory responses. Studies investigating the immune profiles of individuals coinfected with helminths and HIV are scarce. Although it is well known that helminths cause a type 2 immune response during the chronic stage of infection that is characterised by Th2 cell differentiation, eosinophil recruitment, and alternative macrophage activation, the immune mechanisms that regulate tissue damage at the time of parasite invasion are poorly understood. Aim: The aim of the study was to determine the cytokine gene expression profiles during HIV and helminth coinfection in underprivileged South African adults living in a peri-urban area with poor sanitary conditions and a lack of clean water supply. Method: Study participants (n = 164) were subdivided into uninfected controls, HIV-infected, helminth-infected, and HIV and helminth-coinfected groups. The Kato–Katz and Mini Parasep techniques and Ascaris lumbricoides-specific Immunoglobulin E (IgE) and Immunoglobulin G4 (IgG4) levels were used to detect helminth infections. Participants’ HIV status was determined using two HIV1/2 antibody test kits. RNA was isolated from white blood cells for cytokine (Th1-, Th2-, and Th17-related) and transcription factor gene expression profiling using real-time PCR. Results: Multivariate regression data were adjusted for age, gender, BMI, antiretroviral treatment (ART), and nutritional supplement intake. The HIV and helminth-coinfected group had significantly higher tumour necrosis factor alpha (TNF-α) (adjusted β = 0.53, p = 0.036), interleukin 2 (IL-2) (adjusted β = 6.48, p = 0.008), and interleukin 17 (IL-17) (adjusted β = 1.16, p = 0.001) levels and lower GATA binding protein 3 (GATA3) levels (adjusted β = −0.77, p = 0.018) compared to the uninfected controls. No statistical significance was noted for Th2-related cytokines. Conclusion: The coinfected group had higher proinflammatory Th1- and Th17-related cytokine gene expression profiles compared to the uninfected controls. The findings suggest that pro-inflammatory responses are elevated during coinfection, which supports the hypothesis that helminths have a deleterious effect on HIV immune responses.